Change in physical activity is not associated with change in mental distress among adolescents: The Tromsø Study: Fit Futures - Opdal, Ida Marie; Morseth, Bente; Handegård, Bjørn Helge; Lillevoll, Kjersti; Ask, Helga; Nielsen, Christopher Sivert; Horsch, Alexander; Furberg, Anne-Sofie; Rosenbaum, Simon; Rognmo, Kamilla (BMC Public Health, 2019)
Background : Previous research shows that physical activity has a protective effect on mental distress in adults, but the relationship is less researched and seems more ambiguous for adolescents. Studies in this field have typically been cross-sectional by design and based on self-reported physical activity measures, which are known to be vulnerable to response bias. The aim of this study was to investigate the relationship between change in objectively assessed physical activity as measured by accelerometer and change in mental distress among adolescents using longitudinal data from The Tromsø Study: Fit Futures. Method : This study was based on data from 676 upper-secondary school students (mean age 16.23 years at baseline, 45.26% boys) from The Tromsø Study: Fit Futures. Physical activity, mental distress and covariates were measured at baseline (T1) and follow-up (T2) 2 years later. Physical activity was objectively measured with an ActiGraph GT3X accelerometer over 7 days. Mental distress was measured with the Hopkins Symptom Checklist-10 (HSCL-10). Change score variables were computed as the difference between T1 and T2 in number of steps, number of minutes of moderate to vigorous physical activity (MVPA) and mental distress between T1 and T2, and analyzed using linear regression analysis. Results : Changes in steps per day were not associated with changes in mental distress in neither the crude, partially, nor fully adjusted model. Neither was changes in minutes of MVPA per day. Interaction effects between change in both steps per day and minutes of MVPA and gender were also not statistically significant, nor was the interaction effects between baseline levels of mental distress and physical activity. Conclusion : The results of our study indicate that for adolescents in the sample, change in physical activity is unrelated to change in mental distress over a two-year period.